Strategy In Strengthening Capital Towards MSME Market To Maintain Community Economic Stability During The Covid-19 Pandemic Time - KAHARUDDIN; Ambarita, Rosmita; MUKIDI; Pramono, Rudy; Juliana, Juliana; Purba, Nelvitia (The journal of contemporary issues in business and government, 2021)
The objective of implementing a model strengthening strategy is to collaborate with the government and the private sector to work hand in hand in strengthening capital and increasing the MSME production market to maintain economic stability. Researchers' research method, in this case, is a combination of qualitative and quantitative approaches and methods.In general, qualitative research is carried out by interview and observation methods. Through this method, researchers will analyze the data obtained from the field in detail. Quantitative methods with graphs can be seen that there has been a decline in several aspects, even some of the businesses are threatened with bankruptcy. This condition shows that the data has decreased drastically, decreased turnover and credit financing, and difficulty obtaining raw materials. When viewed from the data from the Ministry of Cooperatives in 2020. From the study results, it can be argued that: Since the outbreak of the Covid-19 pandemic, market uncertainty has made the demand for goods sold by MSME players decreasing so that consumers' needs change. Even though it is full of challenges, the MSME sector still has hopes and opportunities to increase its business scale. To survive amid the outbreak of the Covid-19 pandemic, MSMEs use a strategic trading system to strengthen their capital.